2015
DOI: 10.1016/j.neuroimage.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrates underlying the tendency to accept anger-infused ultimatum offers during dynamic social interactions

Abstract: In managing our way through interpersonal conflict, anger might be crucial in determining whether the dispute escalates to aggressive behaviors or resolves cooperatively. The Ultimatum Game (UG) is a social decision-making paradigm that provides a framework for studying interpersonal conflict over division of monetary resources. Unfair monetary UG-offers elicit anger and while accepting them engages regulatory processes, rejecting them is regarded as an aggressive retribution. Ventro-medial prefrontal-cortex (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 68 publications
5
50
0
1
Order By: Relevance
“…found that anger primes increase systolic blood pressure, speed up reaction times in participants with high anger traits, and enhances activity in the post, which is implicated in the regulation of sympathetic arousal. In another study72, angry reactions induced by unfair offers during social interactions activated clusters in the dorso-rostral pons that correspond to the anatomical location of the locus coeruleus73, a major source for noradrenalin in the brain, thus critically involved in arousal and stress responses7475. Moreover, the raphe nuclei are also located in the region of the pons coherent with the loci co-activated with the amygdala in the present study.…”
Section: Discussionsupporting
confidence: 75%
“…found that anger primes increase systolic blood pressure, speed up reaction times in participants with high anger traits, and enhances activity in the post, which is implicated in the regulation of sympathetic arousal. In another study72, angry reactions induced by unfair offers during social interactions activated clusters in the dorso-rostral pons that correspond to the anatomical location of the locus coeruleus73, a major source for noradrenalin in the brain, thus critically involved in arousal and stress responses7475. Moreover, the raphe nuclei are also located in the region of the pons coherent with the loci co-activated with the amygdala in the present study.…”
Section: Discussionsupporting
confidence: 75%
“…Further support for the relation between vigilance and anger is gained from a recent study showing the high locus coeruleus (LC) activity to interpersonal anger induced by a modified ultimatum game was associated with less anger regulation (Gilam et al, 2015). In fact, it has been recently shown that an increase in this LC activation during interpersonal anger following chronic stress was associated with the manifestation of PTSS (Gilam et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that medial PFC structures regulate threat detection and help us to select an appropriate behavioural response given the broader context 141,142 . For example, the vmPFC is implicated in the regulation of emotion, including aggression 143,144 , and angry rumination is associated with dorsal ACC activity and individual differences in aggression 145 . Orbitofrontal cortex and BLA circuitry are also important in the regulation and maintenance of emotional responses 142 .…”
Section: Altered Arousal and Reactivitymentioning
confidence: 99%